"Stay Strong, Stay Sexy, Stay Native": Storying Indigenous youth HIV prevention activism. Issue 3 (September 2019) - Flicker, Sarah; ,; Wilson, Ciann; Monchalin, Renée; Oliver, Vanessa; Prentice, Tracey; Jackson, Randy; Larkin, June; Mitchell, Claudia; Restoule, Jean-Paul
Background: Taking Action II is a community-based participatory action research project that adopted a strengths-based approach to thinking about Indigenous youth HIV prevention activism. Eighteen diverse Indigenous youth leaders produced digital stories about Indigenizing HIV prevention during the summer of 2012 at a week-long retreat. Youth were interviewed twice: right after they created their stories and again after community screenings. In the summer of 2013, youth reunited to collaboratively analyze the themes and meanings of their stories. Seven overlapping themes emerged that demonstrated how youth see HIV in the context of their lives' and community. The stories make connections between HIV and structural violence, culture and relationships. In particular, in the context of HIV prevention, they focus on (1) the role of family and elders, (2) traditional sacred notions of sexuality, (3) the importance of education, (4) reclaiming history, (5) focusing on strength, (6) Indigenous cosmology and (7) overcoming addictions. In contrast to conventional public health messaging, youth produced stories rarely focused on individual harm reduction strategies. Instead, ideas of Indigeneity and decolonization were foregrounded as key strategies for health promotion work.